Flat metallic surface gratings with sub-10 nm gaps controlled by atomic-layer deposition. (9th August 2016) - Chen, Borui; Ji, Dengxin; Cheney, Alec; Zhang, Nan; Song, Haomin; Zeng, Xie; Thomay, Tim; Gan, Qiaoqiang; Cartwright, Alexander
Abstract: Atomic layer lithography is a recently reported new technology to fabricate deep-subwavelength features down to 1–2 nm, based on combinations of electron beam lithography (EBL) and atomic layer deposition (ALD). However, the patterning area is relatively small as limited by EBL, and the fabrication yield is not very high due to technical challenges. Here we report an improved procedure to fabricate flat metallic surfaces with sub-10 nm features based on ALD processes. To demonstrate the scalability of the new manufacturing method, we combine the ALD process with large area optical interference patterning, which is particularly promising for the development of practical applications for nanoelectronics and nanophotonics with extremely strong confinement of electromagnetic fields.